PENGARUH DESAIN KEMASAN TERHADAP KEPUASAN PELANGGAN UMKN SAKUKATA.CO SALATIGA - Andik Prakasa Hadi; Suryani Suryani; Mars Caroline Wibowo (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
The purpose of this research is to promote t-shirt products from Sakukata.co, and to increase customer satisfaction with packaging design using the QFD method. This type of research is quantitative research. The population in this research are customers who have purchased Sakukata.co products at least once. The sample of this research was selected using Linear Time Function and obtained 40 respondents. This study used primary data from Sakukata.co and questionnaires, the data were analyzed using the Quality Function Deployment (QFD) method.The packaging attributes at Sakukata.co consist of the design, dimensions, capacity, shape, strength, and durability of the packaging. The Respon Teknis that must be in Sakukata.co is the packaging design is modern, simple, informative, elegant, and identical to Sakukata.co. The dimensions of the packaging are the same size as the product and can accommodate additional items for souvenirs (during the promo). Maximum packing capacity for 2 products. Ergonomic, and easy to open and close. The packaging material is not easily damaged, and can protect the product when it rains. Packaging design for primary, secondary and tertiary packaging.The results of the partial or simultaneous regression test show that the packaging attributes have a significant effect on customer satisfaction..